2009
DOI: 10.1089/omi.2008.0067
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA Identification in Enterobacteriaceae Using Synteny and Genomic Backbone Retention II

Abstract: Small RNAs are bacterial counterparts of noncoding RNAs. Increasing evidence being added in the literature indicates that these small RNAs play major roles in prokaryotes both at the transcriptome and proteome levels. Based on comparative genomic studies, we present manually curated small RNA regions in 25 recently completed genomes from Enterobacteriaceae. The study is a continuation of our earlier work that uses the presence of small RNAs sandwiched between specific conserved flanking genes retaining genomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Potential SraG homologs located between the pnp and rpsO genes exist in various enterobacteria, such as Salmonella typhimurium, Shigella flexneri, and Klebsiella pneumoniae (Hershberg et al 2003;Sridhar et al 2009). All the Yersinia species exhibit the rpsO-pnp synteny (i.e., gene co-localization), but in Yersinia pestis an insertion element is annotated in the intergenic region of the rpsO-pnp operon.…”
Section: Discussionmentioning
confidence: 99%
“…Potential SraG homologs located between the pnp and rpsO genes exist in various enterobacteria, such as Salmonella typhimurium, Shigella flexneri, and Klebsiella pneumoniae (Hershberg et al 2003;Sridhar et al 2009). All the Yersinia species exhibit the rpsO-pnp synteny (i.e., gene co-localization), but in Yersinia pestis an insertion element is annotated in the intergenic region of the rpsO-pnp operon.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence analysis demonstrated that sraG also exists in several other enteric bacteria, e.g. Salmonella, Shigella, Klebsiella and Yersinia (Hershberg et al, 2003;Sridhar et al, 2009), and the intergenic location of sraG in these bacteria is the same as reported in E. coli (Sridhar et al, 2009). In Listeria monocytogenes, an sRNA gene named rliD is also located between pnpA and rpsO in a similar way to sraG, although their DNA sequences do not share high similarity (Mandin et al, 2007).…”
Section: Introductionmentioning
confidence: 92%
“…First reported in E. coli , SraG located between pnp (PNPase) and rpsO (30S ribosomal protein S15), is expressed preferentially at late-logarithmic phase, and activated by heat and cold shock treatments ( Argaman et al, 2001 ; Sridhar et al, 2009 ). A comparative sequence analysis with E. coli revealed a SraG homolog in Yersinia species ( Sridhar et al, 2009 ). In Y. pseudotuberculosis 16 proteins were identified as potential regulatory targets of SraG ( Lu et al, 2012 ).…”
Section: Functional Characterization Of Srnas In Yersinia mentioning
confidence: 99%